A Room of One’s Own – Within the Four Walls of Tears of Milica Janković - Putyńska, Urszula (Poznańskie Studia Slawistyczne, 2015)
This paper is an analysis of the work Među zidovima (1932) of Serbian writer from the modernist period – Milica Janković (1881–1939). The article focuses on presenting the innovative elements of her prose which opposed the Serbian literary tradition. The main subject of Među zidovima is a physical disease that affects the mental condition. The article also shows the possibility to read the aforementioned work from an autobiographical perspective, as Milica Janković for many years suffered from bone tuberculosis. This work contains numerous references to her biography. The conclusion of the paper is that Milica Janković, drawing on her own experience, has created an intimate work, in which she described her life with the severe, incurable disease.